Socio-political challenges of marginal religious groups: the Sabbatean movement as a case study - Gencoglu, Halim (School of Languages and Literatures, 2019)
Minority religious communities, like the Sabbateans, have often been labelled and marginalised by mainstream religions. At times, their leaders have been labelled as ‘false messiahs’ by society or the state. To what extent do states play a role in facilitating the integration of diverse groupings? This question is particularly topical in the 21st century context of cross-border migrations, but also a perennial question facing society, as minority religious movements developed throughout history. The study focuses on one of the minority movements in Abrahamic religions, Sabbateanism. It analyses the development of the Sabbateanism by controversial Jewish Rabbi, Shabbetai Tzvi in the Ottoman Empire. Tvzi attracted many followers, but also received criticism from orthodox Jews and others, especially when he converted to Islam. The thesis analyses how the movement evolved during Tzvi’s life, and after his death, and what may have urged his followers to hide their religious identities. It then compares this movement with other controversial minority movements, such as Crypto-Christianity and the Ahmadiyya movement in Islam. This comparison offers insight into the minority groups’ challenges, and into the reasons that they have been labelled as ‘heretical’ in Islamic, Christian and Jewish societies. In terms of methodology, the study draws on unique archival materials from Turkey and Israel, dating back to the 17th century. The thesis traces Turkish-Jewish relations prevailing in Asia from the 7th century onwards, to contextualise the Ottoman state’s approach towards Tzvi and his religious movement. It then analyses the State policies towards Sabbateanism and other minority groups. The study critically examines these instances in world history when minorities have been labelled as heratical and some are still labeled as such, even though “tolerance” and “respect” are considered the hallmark of modernization. The study shows that Ottoman rulers developed an elaborate system to accommodate non-Muslim (Dhimmi) societies within the Islamic state. This is perhaps what inspired Toynbee, who was otherwise critical of the Ottoman Empire, to describe it as close to ‘Plato’s ideal state’. This said, the research findings prompt critical reflections on the role of state policies in Ottoman times and beyond, and the effects of religious and national identities on the assertion and flourishing of minority groups.